PENGGUNAAN MODEL EXAMPLE NON EXAMPLE TERHADAP HASIL BELAJAR TEMATIK SISWA KELAS V MIS BAWARI - Hidayanti, Ratih Dian; Utami, Sri; Margiati, Suhardi (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThis research is to analyze the effect of the implementation the example non example models on learning outcomes tematic of fifth grade students of MIS Bawari Pontianak City. The model used in this study is an experimental method to form the study was Quasi Experimental Design, with experimental design Nonequivalent Control Group Design. The population were all fifth grade students of MIS Bawari Pontianak City. The sample in this research is class V A (control) and V B (experiment) MIS Bawari Pontianak City numbering 69 people. Based on statistical calculations of the  final test experimental class average of 78.79 and learning results of final test control class 71,39 final test data of 3,949 and ttable 1,666, because t (3,949) > ttabel (1.666), so Ha is received. Thus, it can be concluded that there are significant implementation of example non example model to student learning outcomes tematic in the fifth grade MIS Bawari Pontianak City. From the calculation of effect size (ES), obtained by ES of 0.9 (High criteria). This means the implementation of example non example models  the integers summing material influence and being the learning outcomes of students in the fifth grade MIS Bawari City. Keywords : example non example model, Learning Outcomes